Pola Komunikasi Pemasaran Politik Bupati Purwakarta Periode 2008-2013 Studi Fenomenologi Kegiatan "Gempungan" di Kabupaten Purwakarta - . Rohendi (KOM & REALITAS SOSIAL, 2011)
Political communication built in elections and local elections in Indonesia so far, is mostly done through a model campaign dominated by the use of campaign techniques that figured konvensional. Euphoria campaign, brings the crowds, took to the road, a convoy of vehicles, install the flag, to sing and dance. Form of campaigns such as this in addition to providing space of anarchism and clashes between supporters also bias kontenstan accountability in the vision and mission after they were elected.Along with the change in the way this nations democracy, voters think the paradigm is slowly shifting from the Political Party Centre to the Voter Centre. Political ideology that first become a bargaining power for the voters, is now shifted to the fulfillment of wants and needs of voters. The consequence of this is political marketing strategy should place more emphasis on market tastes of voters rather than party ideology or the contestants themselves.Purwakarta Regent phenomenon is still rarely get from a politician who used its power to construct society as well as build his political image. As if to difficult to disentangle whether conducted by the Regent was a building campaign or political campaign. For the people of Sunda principle "karaos nembe kahartos" (feels just understand) enough to convince that the Regent Purwakarta is a leader who still necessary both present and future.The purpose of this study was to explore how the construction of political communication does and how the patterns of political marketing communications are built?. Theoretical perspective in this research study attempts to explain what was done with the activities Gempungan's Purwakarta Regent. Phenomenological approach construction be done in order to explore the communication in the event that subsequent researchers unravel the construction in order to find the patterns of political marketing communications in it.